2015
DOI: 10.1016/j.firesaf.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Fire design method for concrete filled tubular columns based on equivalent concrete core cross-section

Abstract: Ibañez C, Aguado JV, Romero ML, Espinos A, Hospitaler A. Fire design method for concrete filled tubular columns based on equivalent concrete core cross-section. Fire Safety Journal. 2015; 78:10-23. doi: 10.1016/j.firesaf.2015 ABSTRACTIn this work, a method for a realistic cross-sectional temperature prediction and a simplified fire design method for circular concrete filled tubular columns under axial load are presented. The generalized lack of simple proposals for computing the crosssectional temperature fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…A method was proposed in a previous paper [2] which permits evaluating the fire resistance of unreinforced CFT columns of circular cross-section. Again, a brief review of this method is given next for a better understanding of the reader.…”
Section: Review Of the Proposed Simple Calculation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A method was proposed in a previous paper [2] which permits evaluating the fire resistance of unreinforced CFT columns of circular cross-section. Again, a brief review of this method is given next for a better understanding of the reader.…”
Section: Review Of the Proposed Simple Calculation Modelmentioning
confidence: 99%
“…The subsequent study of the results is presented jointly with the evaluation of the provisions given by Eurocode 4 Part 1.2 [13]. Finally, the assessment of a simple calculation method proposed by the authors in a previous publication [2] is included and the corresponding proposal for the effective length in fire is given.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last three decades, a considerable amount of experimental and theoretical work has been performed to investigate the fire behaviour of CFST columns (Kodur, 2007;Rush et al, 2012), and the simplified formulae for the fire resistance and thickness of fire protective coating of CFST columns have also been proposed (Comite´Europe´en de Normalisation (CEN), 2005; Han et al, 2003;Kodur, 2007;Twilt et al, 1995;Zhao et al, 2010). Recently, Iban˜ez et al (2015) presented a method for the realistic cross-sectional temperature prediction and the simplified fire resistance design of circular CFST columns under axial compression. Moliner et al (2013) reported the fire test results of 24 slender circular CFST columns under eccentric compression, and both normal and high-strength concrete were considered in the tests.…”
Section: Introductionmentioning
confidence: 99%
“…2016; 128:237-55. doi: 10.1016/j.engstruct.2016.09.037 7 temperature field as a preliminary step, for the subsequent calculation of the design axial buckling load, while the code does not provide any simplified method for that purpose. This makes designers feel unwilling to use these methods, and therefore a simplified way for obtaining the cross-sectional temperature field, like that proposed by Ibañez et al [17] for CHS columns, would be of interest for practitioners and ultimately for promoting the use of this type of composite sections. Other way to deal with this drawback, different from the one exposed in this work, was developed by the authors through the concept of an equivalent concrete core cross-section at room temperature [17].…”
Section: Introductionmentioning
confidence: 99%